Networking of the Human Cerebellum: From Anatomo-Functional Development to Neurosurgical Implications - De Benedictis, Alessandro; Rossi-Espagnet, Maria Camilla; de Palma, Luca; Carai, Andrea; Marras, Carlo Efisio (Frontiers in Neurology, 2022)
In the past, the cerebellum was considered to be substantially involved in sensory-motor coordination. However, a growing number of neuroanatomical, neuroimaging, clinical and lesion studies have now provided converging evidence on the implication of the cerebellum in a variety of cognitive, affective, social, and behavioral processes as well. These findings suggest a complex anatomo-functional organization of the cerebellum, involving a dense network of cortical territories and reciprocal connections with many supra-tentorial association areas. The final architecture of cerebellar networks results from a complex, highly protracted, and continuous development from childhood to adulthood, leading to integration between short-distance connections and long-range extra-cerebellar circuits. In this review, we summarize the current evidence on the anatomo-functional organization of the cerebellar connectome. We will focus on the maturation process of afferent and efferent neuronal circuitry, and the involvement of these networks in different aspects of neurocognitive processing. The final section will be devoted to identifying possible implications of this knowledge in neurosurgical practice, especially in the case of posterior fossa tumor resection, and to discuss reliable strategies to improve the quality of approaches while reducing postsurgical morbidity.